Relevansi Tradisi Keilmuan Islam Klasik Terhadap Sistem Pendidikan Islam Kontemporer di Pondok Al Asror Gunung Pati Semarang - Aghisna Tsanil Mafasa; Ana Zahratun Nisa; Melinda Wahyu Ningrum; Umi Lailatul Maghfiroh; Anom Dwiyantoro; Rikza Chamami (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This research traces the role of classical Islamic intellectual traditions in shaping the direction and character of the contemporary Islamic education system at the Al Asror Islamic Boarding School, Gunung Pati, Semarang. This study highlights the preservation and adaptation of the main elements of turats such as the study of the yellow book, sanad-based teacher-student relations, oral learning patterns, and the development of manners and learning ethics which are maintained as the methodological foundation of Islamic boarding schools. In the context of educational modernization, this study observes how the tradition undergoes adjustment without losing its epistemological roots. Using a qualitative approach, this study explores classroom learning practices, curriculum structure, and views of pesantren stakeholders through observation, in-depth interviews, and document analysis. Field findings show that the Al Asror Islamic Boarding School is able to combine classical scientific heritage with modern educational needs, including the implementation of more systematic learning strategies, strengthening curriculum management, and the use of digital technology as a means of supporting learning. The synergy between traditional values and the demands of this era confirms that turats are not only relevant, but also remain a source of values, ethos, and a framework of thinking that enriches Islamic boarding school educational innovations. Furthermore, the results of the study emphasize that the ability of pesantren to harmonize classical intellectual heritage with social, technological, and pedagogical developments is a strategic factor for the resilience, continuity, and competitiveness of Islamic education in the modern era.